Dapatkah Anda Menangani Tekanan? - I Putu Dharmawan Pradhana; I Wayan Abimayu Angga Nugraha; Ketut Elly Sutrisni (Jurnal Manajemen, 2024)
This research was conducted to find out how the efforts of employees at BRI Bank Teuku Umar Sub-Branch Office in overcoming the workload pressure received so that the performance of each employee can be maintained so as to avoid turnover intention (intention to change jobs). This study uses qualitative data types that use 6 people as research informants. Determination of informants using purposive sampling technique, by way of observation, interviews and documentation. The results obtained from this study are that the workload pressure received by employees at BRI Bank Teuku Umar Sub-Branch Office does not decrease employee performance, because each employee has a way to deal with stress resulting from work pressure received. efforts to overcome this pressure in the form of taking leave, exercising, traveling with family to carrying out hobbies that are liked, so that the perceived work pressure does not affect employee performance and intentions to move jobs from the company.